A New Method for Inducing a Depression-Like Behavior in Rats - Zeldetz, Vladimir; Natanel, Dmitry; Boyko, Matthew; Zlotnik, Alexander; Shiyntum, Honore N.; Grinshpun, Julia; Frank, Dmitry; Kuts, Ruslan; Brotfain, Evgeni; Peiser, Jochanan (Journal of visualized experiments, 2018)
Contagious depression is a phenomenon that is yet to be fully recognized and this stems from insufficient material on the subject. At the moment, there is no existing format for studying the mechanism of action, prevention, containment, and treatment of contagious depression. The purpose of this study, therefore, was to establish the first animal model of contagious depression. Healthy rats can contract depressive behaviors if exposed to depressed rats. Depression is induced in rats by subjecting them to several manipulations of chronic unpredictable stress (CUS) over 5 weeks, as described in the protocol. A successful sucrose preference test confirmed the development of depression in the rats. The CUS-exposed rats were then caged with naïve rats from the contagion group (1 naïve rat/2 depressed rats in a cage) for an additional 5 weeks. 30 social groups were created from the combination of CUS-exposed rats and naïve rats. This proposed depression-contagion protocol in animals consists mainly of cohabiting CUS-exposed and healthy rats for 5 weeks. To ensure that this method works, a series of tests are carried out - first, the sucrose preference test upon inducing depression to rats, then, the sucrose preference test, alongside the open field and forced-swim tests at the end of the cohabitation period. Throughout the experiment, rats are given tags and are always returned to their cages after each test. A few limitations to this method are the weak differences recorded between the experimental and control groups in the sucrose preference test and the irreversible traumatic outcome of the forced swim test. These may be worth considering for suitability before any future application of the protocol. Nonetheless, following the experiment, naïve rats developed contagion depression after 5 weeks of sharing the same cage with the CUS-exposed rats.